NEXUS OF CREATIVITY, INNOVATION, AND ENTREPRENEURSHIP: A SYSTEMATIC REVIEW OF LITERATURE - Mathushan, P (University of Jaffna, 2019)
In today's globalized business world, the phenomenon of entrepreneurship has been recognized as an overriding phenomenon toward the sustainable economic development of the country. Lucidly, the entrepreneur's mind turns around novel ideas and opportunities for innovation and strives to create more open doors eventually, making a dramatic impact on per-capita income, profit maximization, the lifestyle of the people, the thrust of entrepreneurship to survive and thrive is becoming increasingly more relies on creativity and innovation. Intriguingly, creativity and innovation have grown into most crucial facets within the ground of entrepreneurship because it is increasingly the situation that new markets, or even new market growth, may best be achieved through creative and innovative solutions. Studies of entrepreneurs, entrepreneurship, and growth have catalyzed the identification and promotion of innovative knowledge industries, rendering their economic importance increasingly significant. Thus, creativity and innovation are central concepts in reaping entrepreneurship success. Therefore, it is pivotal to embrace creativity and innovation within an entrepreneurial paradigm. The present study fills lacunae by emphasizing the dominant role of creativity, innovation, and entrepreneurship success.
Keywords: economic development; entrepreneurship; creativity; innovation; opportunities